Effect of physical cues of altered extract media from biodegradable magnesium implants on human gingival fibroblasts. (15th October 2019) - Amberg, R.; Elad, A.; Beuer, F.; Vogt, C.; Bode, J.; Witte, F.
Graphical abstract: Abstract: Volume stable barrier membranes made of magnesium are very promising in Guided Bone Regeneration (GBR) to treat periodontal bone defects in dentistry due to their excellent biocompatibility and biodegradability. During the degradation process the cells are exposed to the alteration of various parameters, so called physical cues, involving surface alterations due to the formed corrosion layer and medium alterations arising from the dissolved corrosion products. Cell migration of human gingival fibroblasts (HGF), as a crucial parameter for optimal healing process in GBR, has been investigated on magnesium membranes and revealed that medium alterations by dissolved corrosion products have a higher impact on cell migration than surface alterations. However, the effect of each altered medium parameter on cell migration has not been adequately studied, but their roles are crucial to explain the slower migration rate on magnesium surfaces compared to titanium and tissue culture plastic surfaces. Our study investigates the single effect of Mg 2+, Ca 2+, H2 and increased osmolality as well as the effect of magnesium extracts, which contain a dynamic mixture of previous parameters on cell migration, proliferation and viability of HGF. We showed that at 75 mM Mg 2+ concentration and at 0 mM Ca 2+, respectively, the cell migration rate is greatly reduced. In complex magnesium extract media, we found that a temporarily increased ratio of Mg 2+ to Ca 2+ conditioned a slow HGF migration rate. Based on these findings and the characterization of supernatants from HGF migration assays on Mg membranes, we propose, that the slower migration rate of HGF can be explained by the altered ratio of Mg 2+ to Ca 2+, caused by increasing concentrations of Mg 2+ and decreasing concentrations of Ca 2+ in the vicinity of the corroding Mg implant, combined with a constantly increased molecular hydrogen concentration in the supernatant. These results are cell type specific and should be checked carefully, if necessary, for Mg implant performance. Statement of Significance: The study is providing a systematic approach to explain the main effects of extract medium parameters (physical cues) such as magnesium or calcium ion concentration, osmolality and dissolved molecular hydrogen and CO2 in cell culture media modified by co-incubating with corroding magnesium implants on the migration rate of human gingival fibroblasts (HGF). This study uncovers for the first time the combinatory effect of slightly increased molecular hydrogen and the change in Mg 2+ /Ca 2+ ratio on HGF cell migration.